REMITANSI DAN PENINGKATAN TINGKAT PENDIDIKAN DAERAH ASAL TKI DI KABUPATEN LOMBOK TIMUR - Rahmat Akbar Kurniawan; Yunia Ulfa Variana (SOCIETY, 2021)
West Nusa Tenggara is the province's fourth largest Indonesian Labor Migran (TKI) senders. East Lombok Regency is a Regency of Indonesia's largest TKI senders. Remittance sent to the NTB amounted to 1.6 Trillion rupiah. The average would reach 142 Billion Rupiah per month or the equivalent of 4.6 Billion Rupiah Per Day assuming 365 days in 1 year. Low HDI East Lombok Regency with abundant resources and high population became a concern. Low education prompted a lot of people in there much be TKI primarily Malaysia. It also encourages management of the remittance that insufficient especially for education. This is due to the low interest of family members for continuing education to a higher level, a source of income only from 1 family member (TKI), TKI depart already incurred the debt when it departs, still lack of education of the TKI cause they are only able to work in the informal sector, the survey results showed there is still yet to use the TKI banking services to remittance TKI, one of which is estimated to be due to the relatively low level of education